From an industrializing city to a global city: Hong Kong economic sociology's changing agenda - Tai-lok Lui (economic sociology. perspectives and conversations, 2021)
Economic sociology in Hong Kong is largely an outcome of growing research on its vibrant economic life since the 1960s. As a British colony (prior to July 1, 1997) with a predominantly Chinese population and undergoing export-oriented industrialization at a rapid pace, Hong Kong attracted the attention of social science researchers, both local and overseas. After the 1949 Revolution, when fieldwork in China became no longer feasible, some anthropologists simply saw Hong Kong (and Taiwan as well) as a substitute for their original fieldtrip destination (Baker 2007, 4). Sociologists, however, did not approach their research site in the same manner. But in the eyes of those sociologists whose conceptual framework was informed by modernization theory, Hong Kong was a Chinese society going through industrialization and modernization (and sometimes using the expression westernization), offering a "laboratory" for analyzing the impacts of social change on a so-called traditional society. Meanwhile, there were also researchers with a labor studies background who considered Hong Kong's success in exporting its manufacturing products to be a result of low wages and poor labor protection. So, in the early days of the development of economic sociology-related research in Hong Kong, it was a blending of sociology, human geography, and labor studies. Researchers, despite differences in their academic disciplines and each thus starting with a different set of research questions, came to unravel the socioeconomic and cultural dynamics underlying Hong Kong's rapidly changing economic structure, institutions, and organizations. (...)
Keywords: 300